Development of one-step fluorescence polarization immunoassay for progesterone - Hong, JY; Choi, MJ (PHARMACEUTICAL SOC JAPAN, 2002)
A one-step fluorescence polarization immunoassay (FPIA) was developed to measure progesterone level using an immunocomplex single reagent (SR), a preequilibrated mixture of antibody and tracer. Several fluorescence-labeled progesterone tracers were synthesized using the combination of two progesterone derivatives, I I 11alpha-hemisuccinyloxyprogesterone (P-11HS) and progesterone-3-(O-carboxymethyl)oxime (P-3CMO), and three fluorescence labels, fluoresceinamine isomer I and 11, and ethylenediamine fluoresceinthiocarbamyl (EDF). Antiserum was prepared using a progesterone-bovine serum albumin (BSA) imunogen. The influence of the tracer label was significantly different in titer and sensitivity for antibody binding. The best pair of antibody and progesterone tracer was selected for the antigen-antibody reaction. They were the antibody produced from P-11HS-BSA immunogen and P-11HS-EDF tracer. One-step FPIA is a speedy, homogeneous type of immunoassay which needs neither incubation nor separation of free and bound analyte to measure fluorescence polarization. The detection limit of progesterone by SR-FPIA is approximately 2.7 ng/ml with 50 mul samples. The performance characteristics are acceptable for standard curve reproducibility (coefficient of variation (CV): 0.6-6.4%), precision (CV: 3-13%), and mean dilution recovery (95-102%). The total assay time for 10 samples is about 7 min. This immunocomplex SR has proven to be stable compared with the respective solutions of antibody and tracer.
Keywords: MONOCLONAL-ANTIBODIES; SOLID-PHASE; FLUOROIMMUNOASSAY; SPECIFICITY; PERFORMANCE; AFFINITY; LIGAND; HAPTEN